An Efficient Environmental Channel Modelling in 802.11p MAC Protocol for V2I - Neelambike S; Chandrika J (Institute of Advanced Engineering and Science, 2017)
Recent development in communication of wireless communication for automobile industry have aided the growth of SITS (Smart Intelligent Transport System) which solves numerous vehicular based communication service concerns like traffic congestion, accidental mishap etc. VANET (Vehicular Ad-hoc Network) a characteristic class of MANET (Mobile ad-hoc Network) which is a fundamental element of SITS in which the moving vehicles inter connected and communicates with each other remotely. Wireless technologies play an important part in assisting both Vehicle to Infrastructure (V2I) and Vehicle to Vehicle (V2V) correspondence in VANET. The existing scheduling technique does not consider the environmental factor which affects the throughput performance and increases packet drop rate which result in degradation of service quality. Here in this work the author propose a RHU (Rural, Highway and Urban) environment model considering the environmental factor. The efficient environmental model algorithm is incorporated into slotted aloha in IEEE 802.11p MAC protocols which aided as a spine for assisting both safety application and non-Safety applications. Experiments are conducted for collision and throughput efficiency for varied traffic load and speed of vehicle. The experimental result shows the proposed environmental model impact on collision and throughput efficiency for varied environment and thus helps improving QoS for VANET application.